Optical coherence tomography angiography of peripapillary vessel density in non-arteritic anterior ischemic optic neuropathy and demyelinating optic neuritis - Xiao, Qing; Sun, Chuan-bin; Ma, Zhiqiong (Frontiers in Neurology, 2024)
In cases of optic disc edema or a pale optic disc, distinguishing an episode of optic neuritis (ON) from that of nonarteritic anterior ischemic optic neuropathy (NAION) upon clinical examination is difficult. Optical coherence tomography angiography (OCTA) can reveal differences in peripapillary vascular network structures and provide biomarkers for differential diagnosis. Methods: Twenty-three eyes with NAION, 22 eyes with demyelinating ON(DON), and 27 eyes from healthy participants were imaged using OCTA to observe the radial peripapillary capillaries (RPC).Optical coherence tomography was used to measure the peripapillary retinal nerve fiber layer (RNFL) thickness and the macular ganglion cell complex (mGCC). Data for all patients were recorded at 2-3 weeks and more than>3months after symptom onset.Results: A total of 23 affected eyes from 23 patients with NAION (average age 52.17 ± 7.92 years), 22 eyes from 22 patients with demyelinating optic neuritis (DON) (average age 47.88 ± 19.24 years), and 27 eyes from 27 healthy people (average age 46.43 ± 14.08 years) were included in the study.There were no significant differences in sex, age, and eye laterality between every two groups (F = 0.968, 0.475, 0.870; p > 0.05). Throughout NAION and DON, the superior RPC, superior mGCC, and peripapillary RNFL decreased with time (p < 0.05). In contrast, the inferotemporal RPC and inferior mGCC did not decrease from acute to chronic stage in NAION (t = 1.639, 0.834, p = 0.117,0.413). Compared with the normal group, patients with NAION and DON showed a sharp reduction in the average RPC, RNFL, and GCC from acute to chronic (p < 0.05). Patients with DON had significantly decreased inferotemporal RPC and inferior mGCC compared with patients with NAION (p < 0.05). In contrast, there were no significant differences in the inferior mGCC at the chronic stage between patients with NAION and ON (t = 2.547, p = 0.093). Conclusions: Different structural and microvascular changes were observed in patients with NAION and ON, indicating different features of the optic nerve during the different courses of NAION and ON. Peripapillary vascular density, measured using OCTA, may be a biomarker to distinguish NAION from ON.